DIGITALIZATION PROCESSES AND THEIR IMPACT ON THE DEVELOPMENT OF THE REPUBLIC OF KAZAKHSTAN - G. Alibekova; M. Bapiyeva (Scientific Journal of Pedagogy and Economics, 2019)
The global economy is on its way to digital transformation. The processes of the digital economy are actively continuing in all developed countries, affecting all spheres of life. Numerous studies show a significant dependence of the level of economic development on the indicators of access and use of information and communication technologies (ICT) by enterprises and the public. International organizations are involved in research on maximizing benefits for the growth of the value added of business and society and the potential to minimize losses from digitalization. The analysis of state and interstate program documents, the scientific literature and the most important indices of the development of information and communication technologies and digitalization allows generalizing the main factors of the development of the digital economy: - high innovation activity in the economy as a fundamental factor determining the potential for generating new ICT solutions; - infrastructure that provides access and use of ICT by the population of the country (citizens, companies, government services and departments); - human potential ensuring production, on the one hand, and consumption (use) of new information and communication technologies, on the other hand.